The Correction of Two Verses from Shahnameh Jalal Khaleqi Motlagh - Ali Soleimani; Mohammad Foladi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Many lexicographers, commentators and correctors of Shahnameh have considered the words "Junagh" and "Junna" as one word and have used them instead of each other; However, paying attention to the contextual context, in-text cues, and a comprehensive look at the verses in which these two words appear, indicate that in Shahnameh these two words are not one word but are two words with two different meanings. Although the main purpose of this study is to correct verses from the scientific-critical correction of Jalal Khaleghi Motlagh, the authors, referring to other corrections of Shahnameh such as: Moscow, Jules Moll, ancient letter and Azizullah Jovini Shahnameh, tried to show and eliminate the errors in these corrections. Through this study, it was concluded that the words "Jenagh" and "Jana" have the ability to associate with the words "Leopard (Palang)" and "Choob e Khadang", respectively, and not paying attention to the different meanings of these two words, their companion capacity and avoiding relying on the Florence version, Khaleghi Motlagh did not follow the right path in correcting two verses in which these two words appear. In this research, in addition to correcting those two verses, the problems found in other corrections of Shahnameh were also pointed out. Also, in line with the discussion, a verse of Barzunameh of Shamsuddin Mohammad Kosaj was corrected.